Here's the resulting equation for $n = 3$, which is a little bit different than the traditional $3$-D cross product:
result[0] += v(0, 1) v(1, 2)
result[0] -= v(0, 2) v(1, 1)
result[1] += v(0, 0) v(1, 2)
result[1] -= v(0, 2) v(1, 0)
result[2] += v(0, 0) v(1, 1)
result[2] -= v(0, 1) v(1, 0)
For $n = 7$, the terms look quite unlike those from the traditional $7$-D cross product:
result[0] += v(0, 1) v(1, 2) v(2, 3) v(3, 4) v(4, 5) v(5, 6)
result[0] -= v(0, 1) v(1, 2) v(2, 3) v(3, 4) v(4, 6) v(5, 5)
result[0] -= v(0, 1) v(1, 2) v(2, 3) v(3, 5) v(4, 4) v(5, 6)
result[0] += v(0, 1) v(1, 2) v(2, 3) v(3, 5) v(4, 6) v(5, 4)
result[0] += v(0, 1) v(1, 2) v(2, 3) v(3, 6) v(4, 4) v(5, 5)
result[0] -= v(0, 1) v(1, 2) v(2, 3) v(3, 6) v(4, 5) v(5, 4)
result[0] -= v(0, 1) v(1, 2) v(2, 4) v(3, 3) v(4, 5) v(5, 6)
result[0] += v(0, 1) v(1, 2) v(2, 4) v(3, 3) v(4, 6) v(5, 5)
result[0] += v(0, 1) v(1, 2) v(2, 4) v(3, 5) v(4, 3) v(5, 6)
result[0] -= v(0, 1) v(1, 2) v(2, 4) v(3, 5) v(4, 6) v(5, 3)
result[0] -= v(0, 1) v(1, 2) v(2, 4) v(3, 6) v(4, 3) v(5, 5)
result[0] += v(0, 1) v(1, 2) v(2, 4) v(3, 6) v(4, 5) v(5, 3)
result[0] += v(0, 1) v(1, 2) v(2, 5) v(3, 3) v(4, 4) v(5, 6)
result[0] -= v(0, 1) v(1, 2) v(2, 5) v(3, 3) v(4, 6) v(5, 4)
result[0] -= v(0, 1) v(1, 2) v(2, 5) v(3, 4) v(4, 3) v(5, 6)
result[0] += v(0, 1) v(1, 2) v(2, 5) v(3, 4) v(4, 6) v(5, 3)
result[0] += v(0, 1) v(1, 2) v(2, 5) v(3, 6) v(4, 3) v(5, 4)
result[0] -= v(0, 1) v(1, 2) v(2, 5) v(3, 6) v(4, 4) v(5, 3)
result[0] -= v(0, 1) v(1, 2) v(2, 6) v(3, 3) v(4, 4) v(5, 5)
result[0] += v(0, 1) v(1, 2) v(2, 6) v(3, 3) v(4, 5) v(5, 4)
result[0] += v(0, 1) v(1, 2) v(2, 6) v(3, 4) v(4, 3) v(5, 5)
result[0] -= v(0, 1) v(1, 2) v(2, 6) v(3, 4) v(4, 5) v(5, 3)
result[0] -= v(0, 1) v(1, 2) v(2, 6) v(3, 5) v(4, 3) v(5, 4)
result[0] += v(0, 1) v(1, 2) v(2, 6) v(3, 5) v(4, 4) v(5, 3)
result[0] -= v(0, 1) v(1, 3) v(2, 2) v(3, 4) v(4, 5) v(5, 6)
result[0] += v(0, 1) v(1, 3) v(2, 2) v(3, 4) v(4, 6) v(5, 5)
result[0] += v(0, 1) v(1, 3) v(2, 2) v(3, 5) v(4, 4) v(5, 6)
result[0] -= v(0, 1) v(1, 3) v(2, 2) v(3, 5) v(4, 6) v(5, 4)
result[0] -= v(0, 1) v(1, 3) v(2, 2) v(3, 6) v(4, 4) v(5, 5)
result[0] += v(0, 1) v(1, 3) v(2, 2) v(3, 6) v(4, 5) v(5, 4)
result[0] += v(0, 1) v(1, 3) v(2, 4) v(3, 2) v(4, 5) v(5, 6)
result[0] -= v(0, 1) v(1, 3) v(2, 4) v(3, 2) v(4, 6) v(5, 5)
result[0] -= v(0, 1) v(1, 3) v(2, 4) v(3, 5) v(4, 2) v(5, 6)
result[0] += v(0, 1) v(1, 3) v(2, 4) v(3, 5) v(4, 6) v(5, 2)
result[0] += v(0, 1) v(1, 3) v(2, 4) v(3, 6) v(4, 2) v(5, 5)
result[0] -= v(0, 1) v(1, 3) v(2, 4) v(3, 6) v(4, 5) v(5, 2)
result[0] -= v(0, 1) v(1, 3) v(2, 5) v(3, 2) v(4, 4) v(5, 6)
result[0] += v(0, 1) v(1, 3) v(2, 5) v(3, 2) v(4, 6) v(5, 4)
result[0] += v(0, 1) v(1, 3) v(2, 5) v(3, 4) v(4, 2) v(5, 6)
result[0] -= v(0, 1) v(1, 3) v(2, 5) v(3, 4) v(4, 6) v(5, 2)
result[0] -= v(0, 1) v(1, 3) v(2, 5) v(3, 6) v(4, 2) v(5, 4)
...